Extent of application of green productivity standards in AlSumoud Refinery in Baiji: case study - Baser K. Khazeal; Mohamed A. Hafez; Zakaria Che Muda; Nur Irfah Mohd; Nazaruddin Abdul Taha (NSP Natural Sciences Publishing Cor., 2023)
The study's objective is to ascertain the proportion of implemented green productivity standards, identify implemented green productivity standards, and identify deficiencies in Al-Sumoud Baiji Refinery's dedication to enhancing productivity and safeguarding the environment in crude oil refining. The data was gathered via on-site visits to businesses, direct observation of work activities, and personal interviews conducted with engineers, chemists, and administrative personnel. The primary results suggest that the Al-Sumoud Baiji Refinery has demonstrated a favorable inclination toward diminishing solid and gaseous waste, thereby decreasing environmental harm and decreasing environmental harm and enhancing production. The adoption of green productivity standards is commendable, with the highest level of employee participation suggesting a strong awareness among workers about minimizing pollution and industrial emissions. Refinery management offers education courses to foster this awareness. This strategy mitigates adverse environmental effects and enhances productivity in oil refining.